2016
DOI: 10.1002/smll.201601473
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Induced Emission Fluorogens Based Nanotheranostics for Targeted and Imaging‐Guided Chemo‐Photothermal Combination Therapy

Abstract: Nanotheranostics for biomedical imaging-guided cancer therapy have attracted increasing interest due to their capabilities of both precise tumor diagnosis and high therapeutic efficacy. Among the diverse imaging models, fluorescence imaging have been extensively researched for their high sensitivity, simple operation, and low cost. In this work, aggregation induced emission (AIE) fluorogens based targeted nanotheranostics are facilely fabricated via paclitaxel (PTX) induced assembly of proteins for the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…Tang's group loaded aggregation-induced emission (AIE) dyes into an albumin-based nanoparticle and achieved good in vivo tumor fluorescence imaging 124 , 125 . The AIE dye could be co-loaded with paclitaxel and polypyrrole (PPy) in albumin-based nanoparticles 126 . The fluorescence of the AIE dye could guide PPy-based PTT, which synergised with paclitaxel-based chemotherapy.…”
Section: Albumin As a Nanocarrier For Drug Delivery And Bioimagingmentioning
confidence: 99%
“…Tang's group loaded aggregation-induced emission (AIE) dyes into an albumin-based nanoparticle and achieved good in vivo tumor fluorescence imaging 124 , 125 . The AIE dye could be co-loaded with paclitaxel and polypyrrole (PPy) in albumin-based nanoparticles 126 . The fluorescence of the AIE dye could guide PPy-based PTT, which synergised with paclitaxel-based chemotherapy.…”
Section: Albumin As a Nanocarrier For Drug Delivery And Bioimagingmentioning
confidence: 99%
“…Recently, an AIEgen-based theranostic nanoplatform (HSA-PhENH2-PPy-PTX-cRGD) involving FLI-thermal imaging-guided chemo-photothermal combination therapy was designed and prepared 20 . This nanoplatform was comprised of an AIE unit, a cRGD fragment, a PTT agent polypyrrole (PPy) and a CHT agent paclitaxel (PTX).…”
Section: Recent Developmentmentioning
confidence: 99%
“…In addition, H&E staining revealed that neither significant organ damage nor inflammation was found, suggesting the good bio-compatibility of HSA-PhENH2-PPy-PTX-cRGD NPs. Its good diagnostic ability and excellent therapeutic efficacy made this theranostic system promising for further improving multimodal imaging and imaging-guided cancer treatment 20 .…”
Section: Recent Developmentmentioning
confidence: 99%
See 2 more Smart Citations